Uncovering the syntax of newspaper editorials: a collective case study of The Star, The Straits Times, The Sun, and The Wall Street Journal - Aziz, Muhammad Nasiruddin; Chai, Moo Hung (Universiti Teknologi MARA, Kedah, 2024)
This study compared the syntax of journalistic pieces, particularly the features and syntactic patterns of newspaper editorials. Four English newspaper editorials were analysed via the two research questions: (i) How are the sentences in The Star, The Straits Times, The Sun, and The Wall Street Journal editorials syntactically structured? and (ii) How do the syntactic structures of the sentences from the four editorials written in different contexts compare to one another? A total of 100 clauses from The Star (Malaysia), The Straits Times (Singapore), The Sun (the United Kingdom), and The Wall Street Journal (The United States) were qualitatively analysed using by Morenberg's syntactic model. The results revealed that the syntactic patterns of the clauses were highly varied and not at all formulaic, indicating considerable originality as the writers went beyond the basic patterns via the employment of dissimilar optional syntactic constituents. Several notable similarities were observed in sentence voice, sentence mood, and the expansion and recurrence of the syntactic patterns identified. The comparison has also yielded two dissimilar features namely, the use of subject ellipsis and the use of conjunctions placed at the beginning of sentences. These features highlight the potential consistency and distinctiveness between the newspaper editorials.